2014
DOI: 10.1136/amiajnl-2014-002840
|View full text |Cite
|
Sign up to set email alerts
|

Depression screening via a smartphone app: cross-country user characteristics and feasibility

Abstract: Smartphone apps can be used to deliver a screening tool for depression across a large number of countries. Apps have the potential to play a significant role in disease screening, self-management, monitoring, and health education, particularly among younger adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
98
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(105 citation statements)
references
References 16 publications
5
98
1
1
Order By: Relevance
“…26 Given the accessibility of smartphones, further investigation of the role of smartphone apps in screening and monitoring psychiatric illness is likely to be useful.…”
mentioning
confidence: 99%
“…26 Given the accessibility of smartphones, further investigation of the role of smartphone apps in screening and monitoring psychiatric illness is likely to be useful.…”
mentioning
confidence: 99%
“…[22][23][24][25][26][27][28][30][31][33][34][36][37][38][39][40][41] Developed by Walter Dick and Lou M. Carey [42][43] in 1978, this model considers the stages of analysis, design/development, implementation and evaluation.…”
Section: Methods Used For Developing Mobile Apps In Healthmentioning
confidence: 99%
“…[42][43]54 This method can be used for a variety of instructional systems -in the present study, the mobile apps. [22][23][26][27][28]34,[38][39] It is also highlighted that the Dick and Carey model is based in various perspectives found in the teaching-learning process, namely: Behaviorism (definition of the components of the instructional strategy); Cognitive Theory (formulation of the presentation of the material/ instructional content, and processing of the information); and Constructivism (analysis of contexts in order to assist the users in the construction of conceptual structures for learning).…”
Section: :109mentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies reported that a large proportion of people with mental and substance use disorders appear to be ready to use the Internet and smartphone apps for health purposes [6,7,8,9,10,11]. Furthermore, people who use such computerized interventions in natural settings, at least those who participate in self-assessment procedures, were repeatedly found to have substantial symptoms [12,13]. …”
Section: Introductionmentioning
confidence: 99%